2001
DOI: 10.1111/0272-4332.214143
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Estimates of Exposure and Cancer Risk from Carbon Tetrachloride Released to the Air from the Rocky Flats Plant

Abstract: Carbon tetrachloride is a degreasing agent that was used at the Rocky Flats Plant (RFP) in Colorado to clean product components and equipment. The chemical is considered a volatile organic compound and a probable human carcinogen. During the time the plant operated (1953-1989), most of the carbon tetrachloride was released to the atmosphere through building exhaust ducts. A smaller amount was released to the air via evaporation from open-air burn pits and ground-surface discharge points. Airborne releases from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…On the other side, it was discovered that not just the liver is affected by CCl 4 intoxication, but also the kidneys are damaged and this could lead to cancer [5]. The kidney is sensitive to CCl 4 [2,5].Therefore, less urine may be formed, leading to a buildup of water and waste products in the body and blood, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other side, it was discovered that not just the liver is affected by CCl 4 intoxication, but also the kidneys are damaged and this could lead to cancer [5]. The kidney is sensitive to CCl 4 [2,5].Therefore, less urine may be formed, leading to a buildup of water and waste products in the body and blood, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is sensitive to CCl 4 [2,5].Therefore, less urine may be formed, leading to a buildup of water and waste products in the body and blood, respectively. Recently, it was reported that there is an increase in the reactive oxygen species production, oxidative stress and a significant decrease in the antioxidant enzymes after CCl 4 injection [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon tetrachloride is used as cleaning and degreasing solvents; extraction, paint, and coating solvents; and as a feedstock to produce other chemicals [29]. Carbon tetrachloride can cause liver cancer and is classified as a probable human carcinogen [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This method consists of three steps: (i) analysis of the chemical product life cycle, (ii) definition of the exposure scenarios and (iii) calculation of the potential risk. Many assessments on very large systems are based on this approach, like territorial chemical risk assessment (Rood et al, [3]). …”
Section: State Of the Art And Open Issuesmentioning
confidence: 99%